2024
DOI: 10.1007/s10462-023-10698-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of predictive uncertainty estimation with machine learning

Hristos Tyralis,
Georgia Papacharalampous

Abstract: Predictions and forecasts of machine learning models should take the form of probability distributions, aiming to increase the quantity of information communicated to end users. Although applications of probabilistic prediction and forecasting with machine learning models in academia and industry are becoming more frequent, related concepts and methods have not been formalized and structured under a holistic view of the entire field. Here, we review the topic of predictive uncertainty estimation with machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 439 publications
0
1
0
Order By: Relevance
“…Based on the professional statistician viewpoint regarding market modelling field, there are few types of statistical models that are appropriate [12] to use in the market research which will be discussed in the next section. Other than traditional mathematical modelling, machine learning is one of the frequently used recently when dealing with uncertainty and big data [8], [15], [19], [20], [4], [5]. Barboza, F., Kimura, H., & Altman, E. [5] use machine learning models to predict bankruptcy and found that machine learning models show improved bankruptcy prediction accuracy over traditional models [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the professional statistician viewpoint regarding market modelling field, there are few types of statistical models that are appropriate [12] to use in the market research which will be discussed in the next section. Other than traditional mathematical modelling, machine learning is one of the frequently used recently when dealing with uncertainty and big data [8], [15], [19], [20], [4], [5]. Barboza, F., Kimura, H., & Altman, E. [5] use machine learning models to predict bankruptcy and found that machine learning models show improved bankruptcy prediction accuracy over traditional models [12].…”
Section: Literature Reviewmentioning
confidence: 99%